Training Seminar on Domestic Violence and Child Abuse - Part 6/24
In September 2000, three programs of the Open Society Institute-Budapest (Network Women’s Program, Network Child Abuse Treatment and Prevention Program, and Network Media Program) hosted the double training for representatives of Eastern Europe and the post-Soviet countries in Budapest, focusing on the issues of family violence and child abuse. Title of Seminar: Law Enforcement Train-The-Trainer Program. Date: 03.09.2000.